Profile of Technological Pedagogical Content Knowledge (TPCK) of Prospective Teachers in Atomic Structure Material - Feghana, Ferghana; Saptono, Sigit; Wiyanto, Wiyanto (Journal of Innovative Science Education, 2019)
The purpose of this study is to analyze the TPCK ability of the prospective teachers in preparing, planning, and implementing of learning on atomic structure material. The type of research is a descriptive study with qualitative design. The research subjects were ten prospective teachers who were implementing the PPL in five Senior High Schools in Banda Aceh. The data collection was done in three stages, identifying the CoRe instrument, analyzingthe teaching plan, observing the prospective teachers learning. Firstly, the results showed the TPCK ability of the prospective teachers in preparing of learning is in a good category, butthe ability in the CK, PK, TCK and TPK components are still low. Secondly, the TPCK ability of prospective teachers in the planning are at the moderate category, but average of the prospective teachers ability in the PK, TPK, PCK, and TCK components are still low. Lastly, the TPCK ability of prospective teachers in implementing of learning is in a good category, but the analysis of the components of PK, CK, TPK and TCK scores of prospective teachers are still low.